SEMANTICS IN THE TEXT OF THE HIKAYAT ACEH: A STUDY OF CONTEXTUAL MEANING - Riyan Maulana; Fahmi Hanifa; Saddam (ALDILAL : Jurnal Ilmu-Ilmu Kebahasaan, 2025)
Like living creatures, language experiences development that automatically results in changes. Changes in language can include changes in phonology, morphology, syntax, and semantics. This study discusses changes in the semantics of the word middle in three literary works from different periods, namely Hikayat Aceh (1625) from the 17th century , Hikayat Siak (1855) from the 19th century, and Belahan Jiwa (2012) from the 21st century. Sentences containing the word middle in the three literary works were inventoried and analyzed using Cruse's (2000) theory of lexical semantics and grammatical semantics. Based on the results of the analysis, the author identified five definitions of the meaning of the word middle in the literary works Hikayat Aceh (1625), Hikayat Siak (1855), and Belahan Jiwa (2012). The five definitions of meaning found include a place between two edges, sela/antara, half/perdua, medium, and around; approximately; more or less. The change that is apparent in the meaning of the word tengah is the elimination of the word tengah which means around; approximately; more or less in the Indonesian used today.